Nuclear bone scintigraphy (NBS): A valuable tool depicting osseointegration at the sites of dental grafts - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2006)
Hydroxyapatite (HA) implants were used as grafting materials to fill some of the root resections in three patients. Two of the patients had previous root resections without implant insertion. Being implanted to the resection sites, the porous structure of HA serves as a framework for vascular and soft tissue ingrowth. Previous reports on the utilization of three phase nuclear bone scintigraphy (NBS) to evaluate the degree of fibrovascular ingrowth into HA dental implants after surgery are scarce. Three cases are described in which bone scintigraphy was performed at 6 months after implant insertion. The images revealed technetium-99m methylenediphosphonate (Tc-99m-MDP) uptake at dental implant sites consistent with vascularization and osteoconduction. The current results strongly indicate that osseointegration is complete. This study demonstrates that NBS is a valuable test in the follow up of osseointegration rate at implantation sites and HA is found to be a good biomaterial for grafting purposes showing high osseointegration rates.
Keywords: osseointegration; hydroxyapatite grafting; bone scintigraphy; root resection; TC-99M MDP; CORALLINE HYDROXYAPATITE; OCULAR IMPLANT; VASCULARIZATION